Reposisi CSR (Corporate Social Responsibility) di Indonesia - atika saraswati (JURNAL POLINTER : KAJIAN POLITIK DAN HUBUNGAN INTERNASIONAL, 2017)
CSR discourse (Corporate Social Responsibility) emerged as an effort to built corporate responsibility to the social neighborhood. Accidentally temporal CSR practices rise the stereotype and skepticism of its worked by some ecologists. This paper attempts to reposition CSR in Indonesia as the scutum protecting entity of corporate exploitation. Through an ecopolitical study inspired by Piers Blake's work and concludes with the ethics of care developed by Carol Gilligan, this paper extend the interpretation of CSR as a ‘zoon politicon’ that demands the transformation of its role and practices in symbiotic mutualism with their neighborhood.